A novel HLA‐B allele, B*07:55, identified by sequence‐based typing. Issue 2 (29th December 2012) - Liu, N.; Zhang, Z.; Shan, X.; Wang, L.; Cui, S.
<x xml:space="preserve">Abstract</x> The novel allele differs from HLA‐B*07:02:01 by a single nucleotide substitution at position 538 in exon 3.